MANAGEMENT OF COMPANIES’ BUSINESS PROCESSES IN A CONTEXT OF INFORMATION TECHNOLOGY (Journal of Information Technologies in Education (ITE), 2012)
The feature of information technology management as one of critical business process of the companies, that has a considerable influence on efficiency of their functioning and success achievement is considered in the article.
Keywords: Management; business process; information technology; companies